Model Pembelajaran Mengaji Berbasis Web Untuk Mempermudah dan Memfasilitasi Proses Belajar Mengaji Bagi Anak-Anak - Angger Brayhan Rubminto (The Indonesian Journal of Computer Science, 2024)
Religious education, especially in learning Quranic recitation, plays a crucial role in building the character and morals of children from an early age. This education provides a strong foundation for their future development. This research aims to develop a web-based learning model, Mengajiku, designed to facilitate the process of learning Quranic recitation, particularly in the introduction of Arabic letters (Hijaiyah), Tajweed, and basic understanding of the Quran. This learning model was developed using the ADDIE approach, which includes analysis, design, development, implementation, and evaluation to ensure its effectiveness for users. The test results show that the majority of users, especially children, responded positively, indicating that this model successfully captured their interest in learning Quranic recitation. The System Usability Scale (SUS) test produced an average score of 82.65, which falls under the "excellent" category, indicating success in terms of usability, ease of use, and user satisfaction. This model is expected to be an effective tool for learning the Quran for children in the digital era.